(untitled) (Research, Society and Development, 2023)
This article aims to investigate how psychologists guide their work through psychoanalytic theory in the contexto of public social assistance policies, contextualizing the history of these policies in Brazil and highlighting the contributions of psychoanalysis. The research methodology used was narrative literature review. The results demonstrate the regulations that have enabled the opening of space for psychologists’ involvement in this scenario. Additionally, they show that psychoanalysts can assist individuals in these institutions, considering their desires as relevant, beyond the demand and necessity. It is concluded that psychoanalysis can contribute to transforming the label of those receiving assistance from "users" to "subjects," taking into account that there is a subject of desire within the subject of rights.